2014
DOI: 10.1093/jac/dku100
|View full text |Cite
|
Sign up to set email alerts
|

Detection of methicillin-resistant Staphylococcus aureus (MRSA) carrying the mecC gene in wild small mammals in Spain

Abstract: This is the first report of MRSA carrying mecC in faecal samples of wild small mammals in Spain. These resistant isolates carried genes of the IEC system, unusual in S. aureus from animals. Wild small mammals could be a reservoir of the mecC gene with important implications for public health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 19 publications
5
54
1
1
Order By: Relevance
“…It has also been linked to zoonotic transmission. [53][54][55][56][57] In the United Kingdom, 0.45% of human MRSA isolates carry mecC and most of these belonged to CC130. 58 In addition, mecC isolates with a similar genetic background (ST130, spa type843) have been identified in human isolates from Scotland and North-West England, where the zoo is located from which these specimens originated.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been linked to zoonotic transmission. [53][54][55][56][57] In the United Kingdom, 0.45% of human MRSA isolates carry mecC and most of these belonged to CC130. 58 In addition, mecC isolates with a similar genetic background (ST130, spa type843) have been identified in human isolates from Scotland and North-West England, where the zoo is located from which these specimens originated.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of S. aureus and MRSA was performed by conventional methods (DNAse assay, catalase and Gram staining) and confirmed by specific PCRs of the nuc (S. aureus specific thermonuclease) and mecA or mecC genes. 13,14 S. aureus isolates were typed by: spa (www.ridom.com), agr, and multilocus sequence typing (MLST) (saureus.mlst.net). 11 spa-and agr-typing were performed for all S. aureus isolates.…”
Section: Methodsmentioning
confidence: 99%
“…A study by Wardyn et al (2012) revealed the isolation of MRSA from cottontail rabbit and a lesser yellow migratory shore bird. Other studies include isolation of MRSA from Wild rat, (Himsworth et al, 2014), wood mice (Gómez et al, 2014) red deer, Iberian ibex, vulture, wild boar (Porrero et al, 2012). In some of the studies, the homologue of mecA gene known as mecC strain (ST398 and ST1) were isolated and suspected to be of livestock and human origin (Porrero et al, 2012).…”
Section: Mrsa In Wildlifementioning
confidence: 99%